Stress in nurses who work at units of intensive therapy - Paiva, Glaziane da Silva; Monteiro, Ana Ruth Macedo (Rev Rene, 2004)
Occupational stress occurs when working conditions demand too much from the worker, with direct consequences in his personal and professional lives. The aim of this study was to learn about the effects of environmental stimuli on the health of nurses who work at general or specialized UITs in the city of Fortaleza-CE in 2003. Data were collected through questionnaires. The outcomes showed that the environment of UITs is full of stimuli that cause occupational stress in various degrees in nurses, which results in alterations at the emotional level, like anxiety; at the behavioral level, like restlessness; and at the organic level, being the gastrointestinal system the most affected. It was possible to conclude that there is stress in the environment of UITs and that this affects negatively the nurse’s physical and mental health, which has direct consequences in his quality of life.